2013
DOI: 10.1128/iai.01209-12
|View full text |Cite
|
Sign up to set email alerts
|

5-Lipoxygenase Activity Increases Susceptibility to Experimental Paracoccidioides brasiliensis Infection

Abstract: Paracoccidioidomycosis (PCM) is a systemic mycosis caused by the thermodimorphic fungus Paracoccidioides brasiliensis. Leukotrienes and lipoxins are lipid mediators produced after 5-lipoxygenase (5-LO) activation that exhibit pro-and anti-inflammatory roles, respectively. Here, we have investigated the contribution of 5-LO enzymatic activity in PCM using an experimental model of P. brasiliensis infection. B6.129 wild-type (B6.129) and 5-LO-deficient (5-LO ؊/؊ ) mice were intravenously inoculated with a virulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…Mice treated with the 5-LO inhibitor (MK 886) presented increased fungal recovery, showing that endogenous production of leukotrienes is associated with a protective immune response. Our study differs in several aspects to the first one [28], especially regarding the route of infection. Our murine experimental model used the intratracheal route that better mimics the infection in the human host.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Mice treated with the 5-LO inhibitor (MK 886) presented increased fungal recovery, showing that endogenous production of leukotrienes is associated with a protective immune response. Our study differs in several aspects to the first one [28], especially regarding the route of infection. Our murine experimental model used the intratracheal route that better mimics the infection in the human host.…”
Section: Discussionmentioning
confidence: 70%
“…The first one showed that levels of leukotrienes and lipoxins were increased in WT-infected mice and that 5-LO −/− mice exhibited diminished fungal growth and increased survival rate compared to WT mice. These data indicate that 5-LO derived products might have a critical role in the exacerbation and severity of PCM [28]. Another study investigated the involvement of leukotrienes in the early stages of experimental PCM in selected mouse lines endowed with maximal or minimal acute inflammatory reactivity, and designated AIRmax and AIRmin, respectively [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When Alox5 deficient mice and corresponding wild-type controls were intravenously inoculated with P. brasiliensis they exhibited an increased survival rate [401]. The disease resistance was associated with augmented nitric oxide production, reduced number of CD4(+)-CD25(+) regulatory T cells and higher levels of gamma interferon as well as interleukin-12 levels in the lungs.…”
Section: Lipoxygenase Isoforms In Infectious Diseasesmentioning
confidence: 99%
“…Mice deficient in the 5-lipoxygenase (5-LO) enzyme, necessary for LTB production, are resistant to P. brasiliensis infection and present reduced number of fungal cells in affected tissues and organs [40].…”
Section: Discussionmentioning
confidence: 99%